The Lunge of Global Ideologies: The Challenges of Pancasila Ideology Education in the Middle of Global Existence in the Era of Globalization - Siti Afifatul Mukaromah; Ari Gusmawan; Jeremiah Munandar (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2022)
Global ideology brings many impacts for the development of a nation's character, especially the younger generation. In the midst of various ideologies that are often not in line with cultural values and national principles, nationalism education is considered to be a middle way as a form for the younger generation in the midst of global ideological attacks. This paper aims to analyze the role of nationalism education in becoming a bulwark of global ideology for the younger generation in three countries: Indonesia, Malaysia, and the Philippines. This study looks at how Pancasila Education, Moral and Character Education, and National Education are able to have a significant impact on strengthening the character of young people. This study uses a mixed approach between empirical and normative, where this research study focuses on nationalism and nationalism education in fortifying young people. Several previous studies on the role of Pancasila Education have been carried out, but none of these studies compare the practice in several countries with different state ideologies and concepts, therefore this research has a high level of urgency and novelty. This study found that Pancasila Education, which is widely practiced in several countries other than Indonesia, is included in Nationalism and Nationality Education, National Ideology Education, and Moral and Character Education as one of the educations that must be taken by students in formal education at all levels of education. In addition, the model of education is adapted to the needs of each school, level of education, and students. This study also emphasizes that this type of education has a significant impact on strengthening the character and sense of nationalism in young people.